THE IMPACT OF CHATGPT ON STUDENTS’ WRITING SKILL IN ENGLISH LEARNING STUDY - Adhita respati anjani (ENGLISH EDUCATION STUDY PROGRAM, FACULTY OF TEACHER TRAINING AND EDUCATION, UNIVERSITAS SRIWIJAYA, 2024)
The rapid advancements in artificial intelligence (AI) have notably transformed education, particularly through tools like ChatGPT. As AI becomes integrated into classrooms, its potential to enhance language learning, especially writing skills, warrants investigation. Writing is essential for language proficiency, yet many students struggle to develop effective writing abilities. ChatGPT, capable of generating human-like text and providing feedback, offers innovative avenues for improving students' writing skills and overall language acquisition. This study aimed to assess the impact of ChatGPT on English language learners' writing abilities using a quasi-experimental design with a pretest-posttest non-equivalent group, involving 71 students (36 in the control group and 35 in the experimental group). Results indicated a significant improvement in the writing scores of the experimental group after using ChatGPT, confirmed by paired-sample t-test analysis. The experimental group also outperformed the control group in the posttest, demonstrating ChatGPT's effectiveness in enhancing writing skills. Additionally, improved reading comprehension was observed in the experimental group, suggesting that ChatGPT may facilitate overall language proficiency. While the study highlights the promise of AI tools like ChatGPT, it acknowledges limitations in sample size and scope, indicating a need for further research on the long-term effects of ChatGPT across diverse educational contexts.